FLOW BOILING HEAT TRANSFER IN A RECTANGULAR COPPER MICROCHANNEL - ÖZDEMİR, MEHMED RAFET (YILDIZ TECHNICAL UNIV, 2016)
Flow boiling characteristics of de-ionized water were tested experimentally in a rectangular copper single microchannel of 1 mm width, 0.39 mm height and 62 mm length. De-ionized water was supplied to the microchannel at constant inlet temperature (89 degrees C) and constant inlet pressure (115 kPa). The mass flux ranged from 200 to 800 kg/m(2)s and the heat flux from 56 to 865 kW/m(2). The heat transfer rate data are presented as plots of local heat transfer coefficient versus vapour quality and distance along the channel. Flow visualization was also conducted using a high-speed, high-resolution camera. The results indicate that unstable flow boiling occurred starting at boiling incipience for all mass flux values. The local heat transfer coefficient depends on heat flux only at very low heat and mass fluxes. At high mass flux, there is no heat flux effect with little dependence on vapour quality after the entry region. The mass flux effect was more complex.
Keywords: flow boiling; microchannel; heat transfer coefficient; flow patterns; instability; 2-PHASE FLOW; PRESSURE-DROP; WATER; FLUX; VISUALIZATIONS; INSTABILITY; PATTERNS